1991
DOI: 10.1152/ajpgi.1991.261.3.g553
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide and nitrosocysteine mimic nonadrenergic, noncholinergic hyperpolarization in canine proximal colon

Abstract: Previous evidence suggests that nonadrenergic, noncholinergic (NANC) inhibitory neurotransmission in visceral muscles may be mediated by nitric oxide (NO). We have demonstrated that NO and the NO carrier S-nitrosocysteine can mimic the hyperpolarization in colonic muscle caused by nerve stimulation. The finding that S-nitrosocysteine breaks down fast enough to cause inhibitory junction potential (IJP)-like hyperpolarizations suggests that NO could be stored as a nitrosothiol in secretory vesicles in nerve term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
77
3

Year Published

1992
1992
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(89 citation statements)
references
References 0 publications
9
77
3
Order By: Relevance
“…In the present study we have found that non-cholinergic excitation occurs simultaneously with NANC inhibition at stimulus frequencies of 5 Hz and above. We have characterized noncholinergic neuronal responses for the first time in the absence of interference from NO, which appears to be the predominant enteric inhibitory transmitter in canine colonic muscles (see Thornbury et al, 1991;Ward et al, 1992b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study we have found that non-cholinergic excitation occurs simultaneously with NANC inhibition at stimulus frequencies of 5 Hz and above. We have characterized noncholinergic neuronal responses for the first time in the absence of interference from NO, which appears to be the predominant enteric inhibitory transmitter in canine colonic muscles (see Thornbury et al, 1991;Ward et al, 1992b).…”
Section: Discussionmentioning
confidence: 99%
“…Noncholinergic excitatory input has usually been observed as a 'rebound' response following cessation of nerve stimulation, yet it is quite possible that the influence of non-cholinergic excitatory neurotransmission occurs throughout the period of stimulation. Since NO has been shown to mediate enteric inhibitory neurotransmission in the canine colon Thornbury et al, 1991;Ward et al, 1992b;Huizinga et al, 1992), this influence can be abolished by addition of arginine analogues that inhibit nitric oxide synthase . In the present study we have used a combination of atropine and arginine analogues to unmask and characterize non-cholinergic excitatory neural responses in the circular muscle of the proximal colon.…”
Section: Introductionmentioning
confidence: 99%
“…5 Some agents (e.g., those that increase cyclic AMP [cAMP] or cyclic GMP [cGMP]) induce relaxation by activating K + channels, inducing hyperpolarization and decreasing Ca 2+ influx. 6 - 7 2) Regulation of [Ca 2+ ]; independent of changes in membrane potential was termed "pharmacomechanical coupling." 4 There are several proposed mechanisms for pharmacomechanical coupling.…”
Section: Regulation Of Myoplasmic [Ca 2+ ]mentioning
confidence: 99%
“…Another suggested Author for correspondence at: Department of Physiology 1, Karolinska Institutet, 171 77 Stockholm, Sweden endogenous compound is hydroxylamine or an analogue thereof (Thomas & Ramwell, 1989). If NO can be stored as a nitrosothiol compound in nerve-terminal vesicles it may be able to function as a classical neurotransmitter, stored and released from vesicles (Thornbury et al, 1991;. Cysteine is the most abundant source of free sulphydryl groups in mammalian tissue (Jocelyn, 1972), and at normal extracellular pH, CYSNO has a biological half-life similar to that of NO.…”
Section: Introductionmentioning
confidence: 99%